Evaluation of BUBR1, MCM2, and GMNN as oral cancer biomarkers - Abrahim, Naíza M.M. [UNESP]; Cavalcante, Roberta B.; Pardini, Maria Inês de M.C. [UNESP]; Rabenhorstc, Silvia H.B.; Ferrasia, Adriana Camargo [UNESP] (Wolters Kluwer, 2024)
Oral cancer is a public health problem worldwide. Late diagnosis results in a low survival rate. However, this tumor can arise from oral precancerous lesions and identification of biomarkers in precursor lesions has the potential for early diagnosis, improving patient survival. In this context, proteins involved in the cell cycle control are potentially promising. This study aimed to evaluate the importance of immunohistochemical expression of BUBR1, MCM2, and GMNN as biomarkers of oral carcinogenesis considering different oral sites. Sixty-six samples of oral epithelial dysplasia (from 33 males and 33 females) and 63 samples of oral squamous cell carcinoma (from 44 males and 19 females) were subjected to immunohistochemistry to detect some human proteins. Ki67 expression was included as a marker of cell proliferation. Marker expression was quantified by manually counting at least 1000 cells, and the labeling index was used in all statistical analyses. GMNN, MCM2, BUBR1 (nuclear and cytoplasmic labeling), and Ki67 expression levels were higher in carcinomas than in dysplasia (P < 0.05). Cytoplasmic BUBR1 was a good marker of malignancy (AUC = 0.8525, P < 0.05), but Ki67 was not (AUC = 0.5943, P = 0.0713). GMNN, MCM2, BUBR1, and Ki67 had higher expression in carcinoma than in dysplasia, regardless of the site of the lesion. Cytoplasmic BUBR1 has the potential to be used as a marker of tumor progression.
Keywords: BUBR1; dysplasia; GEMININ; MCM2; oral carcinoma